MOLECULAR PHYLOGENY OF LEIOGNATHIDAE IN THE WATERS OF PERHENTIAN ISLANDS, TRENGGANU, MALAYSIA - Giat, Seah Ying; Ghaffar, Mazlan Abd.; Usup, Gires (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2008)
Several series of trawl surveys were carried out in the waters of Perhentian Islands using commercial trawlers. 16S mitochondrial rRNA gene sequences were used to infer the phylogenetic relationships among nine morphospecies of leiognathids. The results showed that the genus Leiognathus is paraphyletic, whereas Gazza secutor, Photoplagios, Photopectoralis and Nuchequula are monophyletic. The molecular phylogenetic posions of the leiognathids studied were identical with morphological delineation, except for Photoplagios stercorarius. Branch of P. stercorarius was placed between Photoplagios spp. clade and clade of Secutor and Gazza. P. stercorarius was more affiliated to genus Photoplagios morphologically however have slight different features of light organ system compared with others three Photoplagios sp. caught in this study. It is probable that two distinct subclades occur in genus Photoplagios. Leiognathus equulus formed the base of the other leiognathids. Leiognathus splendens and Leiognathus jonesi formed a sister taxa to Photopectoralis species. Gazza formed a sister taxa to Secutor and Nuchequula formed a sister taxa to the group of trifurcation but toth with low bootstrap support. This study has shown that 16S mitochondrial rDNA is a good marker for phylogenetic analysis of the Leiognathidae.